Determination of Study Motivation and Learning Achievement In Entrepreneurship In The Covid-19 Pandemic Period - Mustofa, Achmad; Amiruddin, Amiruddin; Ismail, Ismail; Sitorus, Destri Sambara; Setiawan, Ananda (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2021)
Indonesia is a country that is affected by the existence of COVID-19. One of the biggest impacts on the world of education at Syiah Kuala University. One of these impacts includes learning conducted online. The purpose of this study was to see the influence of the learning styles of students of Syiah Kuala University Economic Education on learning motivation and subsequently on learning achievement in entrepreneurship courses. This type of research is a quantitative study with descriptive methods. The research design becomes a research model to measure the effect of independent variables, namely learning styles, intervening variables, namely learning motivation, and dependent variables, namely learning achievement. The results showed 1) there was a positive and insignificant influence on the learning style variable on the learning motivation variable, 2) there was a positive and insignificant influence on the learning motivation variable on the learning achievement variable.